Death & Sparkles : Death & Sparkles # 1 - Justus, Rob (San Francisco : Chronicle Books, 2021)
Being Death is a lonely job, especially when everything you touch instantly dies (not to mention the paperwork); but being Sparkles the Last Unicorn is not much fun either, since everyone just wants to take selfies with you or use you to sell stuff--but when Death and Sparkles meet between life and, well, death, it is the beginning of a friendship that just might change the world.
Ages 10.
Grades 4-6.
Keywords: Death -- Comic books, strips, etc; Death -- Juvenile fiction; Unicorns -- Comic books, strips, etc; Unicorns -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Death -- Fiction; Unicorns -- Fiction; Friendship -- Fiction; Graphic novels; Humorous fiction